Safe crossing among pedestrians based on extended theory of planned behaviour - Sundararajan, Komala Devi (2021)
Malaysia is considered one of the countries experiencing rapid growth in motorization, automobile, and transportation systems. Pedestrian in Malaysia has become a very important road user on a daily basis in human society. Creating awareness for the pedestrian to take a safety crossing behaviour is very important to prevent the number of pedestrian accidents and fatalities. This study aimed to investigate the contributing factors that affect pedestrians to use a crossing facility and to analyse the relationship between the contributing factors and a safe crossing behaviour. Furthermore, this study also proposed improvement in crossing facilities to ensure pedestrians cross roads with safe behaviour. In understanding this output, an extension of the well established variables of Theory of Planned Behaviour (TPB) which include Attitude (ATT), Subjective Norm (SN), Perceived Behavioural Control (PBC), Perceived Consequence (PC), Expectation (EX) and Perceived Safety (PS) was used in this study toward using crossing facilities. A questionnaire was designed and distributed to 274 respondents in Batu Pahat. The data were analyzed by Structural Equation Modeling (SEM) using SPSS 20 and AMOS. Goodness of fit for the revised structural model showed GFI, CFI, TLI and NFI were greater than 0.90 and AGFI was less than 0.90. The findings showed that hypothesis testing of all the variables had significant relationship and positive impact on behavioural intention among pedestrians. Therefore, TPB model with extended variables is suitable to predict the behavioural intention towards safe crossing behaviour. As the third objective, researcher have proposed improvements in crossing facilities as “Solar Zebra crossing warning light (SZCWL)” and it was accepted by majority of the respondents (86.1%).